2018
DOI: 10.1371/journal.pone.0192316
|View full text |Cite
|
Sign up to set email alerts
|

XRCC3 Thr241Met and TYMS variable number tandem repeat polymorphisms are associated with time-to-metastasis in colorectal cancer

Abstract: BackgroundMetastasis is a major cause of mortality in cancer. Identifying prognostic factors that distinguish patients who will experience metastasis in the short-term and those that will be free of metastasis in the long-term is of particular interest in current medical research. The objective of this study was to examine if select genetic polymorphisms can differentiate colorectal cancer patients based on timing and long-term risk of metastasis.MethodsThe patient cohort consisted of 402 stage I-III colorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…When analyzing metastasis as a clinical outcome in colorectal cancer, it is observed that not all patients in a population-based cohort experience the outcome despite potentially long follow-up times [3, 4]. Consequently, the long-term metastasis-free survival probability estimate for such a cohort plateaus at a non-zero value.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When analyzing metastasis as a clinical outcome in colorectal cancer, it is observed that not all patients in a population-based cohort experience the outcome despite potentially long follow-up times [3, 4]. Consequently, the long-term metastasis-free survival probability estimate for such a cohort plateaus at a non-zero value.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the long-term metastasis-free survival probability estimate for such a cohort plateaus at a non-zero value. This indicates the study cohort consists of a mixture of long-term metastasis-free survivors as well as patients who are susceptible to metastasis within the follow-up time [3, 59]. Thus, there might be prognostic factors distinguishing long-term metastasis-free survivors from patients who are susceptible to metastasis as well as factors determining timing of metastasis in the susceptible group [5, 6, 10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic polymorphisms of MLH3 rs175057 as well as MSH2 rs3771273, rs10188090 and rs10191478 may predict prognosis in patients with locally advanced rectal cancer who received preoperative chemoradiotherapy 134. XRCC3 Thr241Met polymorphism was associated with time-to-metastasis of CRC135. The specific role of the summarized polymorphisms of our review in clinical application and underlying mechanisms required further studies to elucidate.…”
Section: Summary and Future Directionsmentioning
confidence: 88%
“…Gene polymorphisms of TYMS have been reported to have potential in improving the diagnosis, prevention and treatment of breast cancer (46). Hence, several studies are now focusing on the association between gene polymorphic variations of TYMS with various types of cancer (4749). BIRC5 was upregulated in 76% LUSC samples and the expression in LUSC tissues was significantly higher compared with that in non-cancerous tissues (50).…”
Section: Discussionmentioning
confidence: 99%